Pemberdayaan perempuan: Kompetensi dan kontribusi dalam sektor UMKM - Audyzza, Keysa Fahradine (Maliki Interdisciplinary Journal, 2024)
Empowering women in the Micro, Small and Medium Enterprises (MSME) sector has an important role in reducing poverty, increasing income, and preparing women’s communities to become bank-friendly communities. Women not only play a role in household work, but are also increasingly active in various types of work, including as MSME owners and creative industry players. Empowering women in the MSME sector involves playing a role in providing business capital, production processes, distribution and product marketing. With women’s empowerment, it is hoped that gender equality will be created, the family’s economic welfare will increase, and positive contributions will be made to economic and social development. Efforts to empower women need to continue to be optimized by the government, private sector, banking and various other parties to support the growth of MSMEs and achieve national goals of increasing the number of entrepreneurs and alleviating poverty.